Influence of physical activity on autophagy inducing and reduction of cancer incidence: critical review of physiological and metabolic mechanisms. (Research, Society and Development, 2021)
Objective: To describe the main mechanisms of autophagy stimulated by physical activity and its relationship with the reduction in the incidence of cancer. Material and methods: Data collections were carried out through the analysis of the scientific literature available in the MEDLINE, ScienceDirect and Wiley databases, independently and manually. The terms "cancer", "autophagy" and "physical activity" were used as search descriptors, and the period of time for publications covered the years 1990 to 2020. The inclusion criteria were: "works published within the scope of the study, published in the aforementioned period”. And as an exclusion criterion: “works not related to the study topic and with reports that are already outdated according to current literature”. Results: Physical activity positively influences different systems, leading to acute and chronic changes. The benefits in metabolic, immune, cancerous, cardiovascular, psychiatric and neurological pathologies are indisputable and the mechanisms are being elucidated. Autophagy mediates the digestion and recycling of obsolete cell parts during starvation and participates in a variety of physiological waste removal processes. Autophagy is able to eliminate microorganisms, toxic protein aggregates, genotoxic, playing roles during infection, aging and disease pathogenesis. Conclusion: From the analysis of the mechanisms involved in physical activity-induced autophagy, three main points were postulated: 1) Via mTORC1 inactivated by starvation, 2) Regulation by reactive oxygen species and hypoxia, 3) Regulation of autophagy by alternative pathways to mTORC1.